Endobronchial ultrasound elastography for differentiating benign and malignant lymph nodes - Gompelmann, Daniela; Kontogianni, Konstantina; Sarmand, Nilab; Kaukel, Philine; Krisam, Johannes; Eberhardt, Ralf; Herth, Felix (Respiration, 2020)
Background: Endobronchial ultrasound elastography that provides information on tissue stiffness may help distinguish malignant from benign mediastinal and hilar lymph nodes. Objectives: In this prospective trial, we assessed the diagnostic value of elastographic images and the interobserver agreement in its evaluation. Method: Elastographic images from 77 lymph nodes in 65 patients were reviewed by 3 pneumologists. The elastographic image was classified based on the predominant colour: predominantly green, intermediary, and predominantly blue. With 2 or 3 interobserver matches, the corresponding elastographic image was correlated with the pathological result obtained from endobronchial ultrasound-guided transbronchial needle aspiration (EBUS-TBNA) and/or other invasive procedures. Results: All 3 reviewers had agreement in classifying elastographic images in 45% (35/77). Overall, the interobserver agreement among the 3 readers for classifying elastographic pattern was found to be moderate (Fleiss Kappa index = 0.519; 95% CI = [0.427; 0.611]). On cytological/histological evaluation, 55 lymph nodes were malignant and 22 were benign. In classifying “green” as benign and “blue” as malignant, the sensitivity and specificity were 71% (95% CI = [54%; 85%]) and 67% (95%-CI = [35%; 90%]), respectively. Conclusions: Elastography will not replace invasive EBUS-TBNA due to a moderate interobserver agreement and insufficient sensitivity and specificity. However, elastography will, maybe, present an additional feature to identify malignant lymph nodes in the context of clinical, radiological, and cytological results.